Peredaran Makanan Yang Sudah Kadaluarsa Sebagai Kejahatan Terselubung Terhadap Perlindungan Konsumen - Jody Yaumulqidam; Aughi Nanda Saputra; Faturrahman Vrali,; Libra Yadi Pura; M. Imam Muslim,; Andi Candra (Consensus : Jurnal Ilmu Hukum, 2023)
The trade and barrier-free conditions expected from trade conditions based on the principles of healthy competition are the result of the development of thought towards the modernization of inter-national relations. The shift from the era of closure, monopoly, and protection to the age of openness without protection is the outcome of this development of thinking. Factors that contribute to the hidden crimes of food expiration occurring in the community include traders who may not know or be unaware that they are selling foods that have expired because there are no complaints or grievances from customers. Therefore, they may believe that they can continue to sell foods expiring because they do not want to lose it and want to sell it as long as the goods are still worth selling. However, they might not know that selling expiring foods is a violation of the law.